Kajian Yuridis Mengenai Ketidaktransparanan dalam Penerapan Strategi Up-Selling dan Perlindungan Konsumen - Fatimah Farhania; Siti Aisha Rembulan; Dimas Agung Prasetya; Muhammad Aqiel Nasyrullah (CV Rewang Rencang, 2025)
Up-selling marketing strategies encourage consumers to purchase higher-value products or services but risk harming consumers due to unclear information. This study aims to analyze legal protection under Law No. 8 of 1999 on Consumer Protection, which guarantees consumers’ rights to accurate, clear, and honest information. Using a normative juridical method, the study finds that non- transparent up-selling practices create information asymmetry and potential consumer losses. Therefore, businesses are obliged to provide complete and transparent information so that consumers can make fair and informed purchasing decisions.